(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Cloud computing is emerging as a critical information communication technology to heavily impact our daily life in the future. As computing becomes increasingly pervasive, the energy consumption attributable to computing is climbing that marked the foundation of Green Computing. Green Cloud is an Internet Data Center architecture which aims to reduce data center power consumption, and at the same time guarantee the performance from users’ perspective, leveraging live virtual machine migration technology. Saving energy or reduction of carbon footprints is one of the aspects of Green Computing. Green Cloud Architecture enables comprehensive online-monitoring, live virtual machine migration and VM placement optimization. A Green Cloud System responds to peak utilization periods and adjusts availability of resources based on them expanding or shrinking the cloud as needed. The aim of this paper is a literature study of the challenges and various issues in field of Green Computing and discusses the future scope of Green Clouds. Index Terms: Green Cloud computing, virtualization, security, recycling, data centers, cloud architecture.